[RETRACTED ARTICLE] Business Strategies for a Variety of Changes to Achieve Competitiveness with the World - Meesemkraiseehanart, Prayawee (Journal of Dhamma for Life, 2024)
The objective of the study was to understand how knowledge is shared in organizations, particularly the role of rewards and social units in knowledge transfer in a multicultural context in Dubai, UAE. In this study, we wanted to know how knowledge was shared and considered possible motivations and barriers to knowledge sharing in multicultural organizations. Method of study using quantitative methods. The population in this study included first-level managers in Dubai, United Arab Emirates, by email survey from October to December 2014. Variables in the study include knowledge sharing (y) and individual independent variables (xi) (financial rewards, social units, and cultural diversity) while controlling the impact of others: y= 60 +61*x1+62*x2+b3*x3+e; where b regression weights to minimize the sum of squared deviations and the residual error. Analyze data using descriptive statistics. The results of the study found that: For the first research question, the null hypothesis is rejected, indicating a positive relationship between rewards for knowledge sharing and knowledge-sharing behavior in multicultural organizations. The second null hypothesis is not rejected, indicating there are not sufficient data to prefer the alternative hypothesis to the null hypothesis. The third null hypothesis is also not rejected, indicting there are not sufficient data to conclude there is a positive relationship between the cultural diversity of the organization and knowledge sharing within the organization. Findings also revealed a positive relationship between the combined effect of rewards, social units, and cultural diversity and knowledge sharing.